Nature of Airway Inflammation by Phenotype of Severe Bronchial Asthma in School-Age Children - Ye.P. Ortemenka (Zaslavsky O.Yu., 2015)
At the premises of regional clinical hospital of Chernivtsi city, the nature of airway inflammation has been studied in 43 schoolchildren with persistent bronchial asthma for the purpose of individual choice of antiinflammatory basic therapy. The first (I) clinical group consisted of 24 children with severe asthma phenotype, the second (II) one included 19 children with moderate to severe course of the disease. Cytological analysis of induced sputum was carried out by the method of I.D. Pavord. Patients with severe bronchial asthma are characterized by more significant hypereosinophilic reaction of airways. Thus, a significant eosinophilia (sputum eosinophils ≥ 12 %) of bronchial mucous was determined in 29.2 % of patients with severe asthma and in 10.5 % (Pϕ < 0.05) of cases in the second group. At the same time, the relative moderate airway lymphocytosis (sputum lymphocytes ≥ 11 %) has been detected in 31.6 % of patients in the second group and in 25.0 % of schoolchildren with severe asthma (Pϕ > 0.05). Number of cylindrical epithelial cells in bronchial mucous ≥ 50 % was registered in 29.3 % of patients from the I group and in 26.3 % of schoolchildren from the second comparison group (Pϕ > 0.05). School-age children with severe asthma are characterized by hypereosinophilic-moderate-lymphocytic type of airway inflammation associated with their significant remodeling that, in general, require the administration of high doses of inhaled corticosteroids in combination with antineutrophilic (antileucotriens, immunoglobulin E blockers) antiinflammatory drugs.